2005
DOI: 10.1287/mnsc.1050.0433
|View full text |Cite
|
Sign up to set email alerts
|

Better, Faster, Cheaper: An Experimental Analysis of a Multiattribute Reverse Auction Mechanism with Restricted Information Feedback

Abstract: The majority of reverse auctions for procurement use a single-attribute (price) format while providing constraints on nonprice attributes such as quality and lead time. Alternatively, a buyer could choose to conduct a multiattribute auction where bidders can specify both a price and levels of nonprice attributes. While such an auction may provide higher theoretical utility to the buyer, it is not clear that this theoretical improvement will be realized given the increased complexity of the auction. In this res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(68 citation statements)
references
References 24 publications
1
61
2
1
Order By: Relevance
“…On the other hand, Shachat and Swarthout (2010), find that an EA with buyer assigned bidding credits can provide better outcomes than the FPA for both suppliers and sellers. There is also a large and promising literature on successful reverse auction examples where the quality is determined within the reverse auction, for example Chen-Ritzo et al (2005) and Parkes and Kalagnanam (2005).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Shachat and Swarthout (2010), find that an EA with buyer assigned bidding credits can provide better outcomes than the FPA for both suppliers and sellers. There is also a large and promising literature on successful reverse auction examples where the quality is determined within the reverse auction, for example Chen-Ritzo et al (2005) and Parkes and Kalagnanam (2005).…”
Section: Discussionmentioning
confidence: 99%
“…Even the laboratory experiments showed encouraging results. Multi-attribute auctions with three different settings were experimented in laboratories: (1) with buyer's scoring function fully revealed for two attributes (Bichler, 2000), (2) with buyer's scoring function not revealed for three attributes (Strecker, 2003), and (3) with partial revelation of the scoring function for three attributes (Chen-Ritzo et al, 2005). All the three showed that multi-attribute auction formats outperform single attribute auctions.…”
Section: Configurable Bidsmentioning
confidence: 99%
“…Experiments by Bichler (2000) and Chen-Ritzo et al (2005) indicate that MA auctions outperform PO auctions in terms of efficiency, buyer utility, and supplier profits. However, subjects were not incentivized to provide more than the minimum effort on non-price dimensions.…”
Section: Introductionmentioning
confidence: 98%